electronic payments in Mozambique: a Baseline on their adoption in Maputo and Matola - Ortigão, Margarida Simão Ramalho (2015)
This study analyses the access and use of financial services by small business owners in the cities of Mozambique, as an important tool for boosting economic growth and diminishing inequality. It correlates owners’ and business characteristics with the probability of adopting Points-of-Sale (POS), Mobile Banking and Mobile Money in everyday transactions. The main findings highlight that what mostly affects the use of POS is the size of business and the volume of transactions (positively correlated with POS adoption), while using mobile phone technologies for payments predominantly depends on the owner’s age and whether he/she is a frequent cellphone user. Moreover, to increase the use of electronic means of payment it is necessary to increase financial literacy and improve the banking services.